LIVING IN REACH OF HUMANITY’S LIFE-SUPPORT SYSTEM - KILBEN, GILL MC; KOAUL MARSHAL; RMETTE PARON (International Journal of Multidisciplinary Research and Studies, 2021)
The paper addresses the state-of-knowledge of complex adaptive systems — including their operation via cycles of innovation and co-adaptation — to sustain continuous, whole-system complexity and full-functionality. Emerging understanding of how humanity can live gratefully inside advanced adaptive systems (Planet Earth, ecosystems, cities, etc.). Strategies of Appreciative Inquiry – as the model for decision-making and strategic change — that provide the data needed to live appreciatively, co-adapt with complexity, and thrive by living within complex systems. Explores the integrative management of energy, water, and food systems –WEF Security Nexus — as the catalyst for living within complex systems; and how integrative management builds self-reliance and local Eco-entrepreneurs essential to achieving the global goal of sustainability. Overview of Sustainable Communities Institute’s (SCI) application of knowledge about complex systems, living appreciatively, and AI strategies to help communities interconnect sustainability’s triple bottom line — ecological, social and economic — with appreciative system dynamics, to empower communities to thrive by living sustainably. How SCI facilitates an appreciation of ecological systems as primary human supports, infrastructural systems as secondary supports, and the built-environment as tertiary supports; and sustainable development as a synergy of the three to sustain full-functionality of the complex system upon which we rely. Overview of SCI projects including ones focused on optimizing the WEF Security Nexus and others focused on enhancing the ability of a key system – e.g., food system — to catalyze community change to thrive in the current context of accelerating system change. Concludes with a discussion of new potential unleashed by integrative managing the WEF Security Nexus and the three levels of human supports as the catalyst for living sustainably; tools for assessing the degree to which this change is occurring, and adaptive processes for facilitating the emergence of community self-reliance and the ability to thrive during the current turbulent time of complex system change.